Dampak Berpengaruhnya Perencanaan Pajak Terhadap Efisiensi Beban PPh Pasal 21 - Misto Ketaren (CERED Indonesia Institute, 2021)
Tax planning is one of the functions of tax management (tax management) through tax planning so that income tax can be reduced optimally by legal means. The purpose of tax planning is not to avoid paying taxes, but to arrange so that the tax paid is not more than the amount that should be the company's obligation. In the implementation of tax planning, it is very necessary to have good knowledge of the applicable tax laws and regulations. The company must really understand all tax rules, so as not to get caught in the problem of tax evasion or other illegal efforts or violate the applicable tax provisions, so that the company must bear the consequences of being subject to sanctions that will harm the company.